CALEB’S CHARACTERIZATION ON THE MOVIE OF FIREPROOF DIRECTED BY ALEX KENIDRICK AND STEVEN KEDNDRICK: Hierarchy Needs Study by Maslow - Kusuma, Ilona Viviana; Rahman, Irpan Ali (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2022)
The research aimed to analyze about the characterization of the main character and to reveal the Self Esteem of the main character on “Fireproof” directed by Alex Kendrick and Steven Kendrick in 2008. In this research, the writer uses hazo and Claudio Naranjo’s (1950) concept, which divided characterization into nine parts. To support the research, the writer use Abraham Maslow theory about Self Esteem Characterization. In the theory, explain about how people face life with more confidence, kindness, optimism, and aspects that lead on setting and achieving one’s objectives. The writer use qualitative method approach in which taking the quotes as the evidence to support analyzing the research. After doing the research, the writer discovered that Caleb as the main character has various Characterization. He also has a strong esteem to fix his household problem and maintain his marriage.